Guilt in Games - Battigalli, Pierpaolo; Dufwenberg, Martin (American Economic Review, 2007)
“A clear conscience is a good pillow.” Why does this old proverb contain an insight? The emotion of guilt holds a key. Psychologists report that “the prototypical cause of guilt would be the infliction of harm, loss, or distress on a relationship partner” (Roy Baumeister, Arlene M. Stillwell, and Todd F. Heatherton 1994, 245; June Price Tangney 1995). Moreover, guilt is unpleasant and may affect behavior to render the associated pangs counterfactual. Baumeister, Stillwell, and Heatherton state, “If people feel guilt for hurting their partners ... and for failing to live up to their expectations, they will alter their behavior (to avoid guilt) in ways that seem likely to maintain and strengthen the relationship.” Avoided guilt is the down of the sound sleeper’s bolster. How can guilt be modeled? How are human interaction and economic outcomes influenced? We offer a formal approach for providing answers. Start with an extensive game form which associates a monetary outcome with each end node. Say that player i lets player j down if as a result of i’s choice of strategy, j gets a lower monetary payoff than j expected to get before play started. Player i’s guilt may depend on how much he lets j down. Player i’s guilt may also depend on how much j believes i believes he lets j down. We develop techniques to analyze equilibria when players are motivated, in part, by a desire to avoid guilt. The intellectual home for our exercise is what has been called psychological game theory. This framework—originally developed by John Geanakoplos, David Pearce, and Ennio Stacchetti (1989) and recently extended by Battigalli and Dufwenberg (2005) (henceforth B&D)—allows players’ utilities to depend on beliefs (about choices, states of nature,